Frascati Manual and Evolution in the Collection of Data on Work to Create New Knowledge - Kuusisto, Jari; Flowers, Stephen (De Gruyter, 2024)
The world continues to change, and the way that R&D takes place also continues to evolve. This chapter explores how the Frascati Manual was repeatedly revised in order to reflect the many changes in the economies, industrial structures and political priorities of OECD (Organisation for Economic Co-operation and Development) member nations. It reviews the development and revision of the collection of data concerning research and development (R&D) by the OECD and laid down in the Frascati Manual. This chapter will also explore the standardisation of R&D measurement, the increasing share of intangibles and the challenges in measuring R&D in services and software contexts. It will provide a detailed summary of the core definitions of R&D activity contained within the Frascati Manual and explore how the approach to data collection has been revised over seven editions since the introduction of the manual in 1963. This chapter explores how these revisions were made in response to changes in the world economy and the new ways of undertaking R&D that continue to emerge. The challenges to data collection faced by such approaches are examined and the chapter concludes by questioning how well the manual actually reflects the changing world of R&D and raises a series of issues that provide directions for further research in this area.